Ananas comosus: Pineapple - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document provides an overview of the pineapple plant, Ananas comosus, detailing its characteristics, uses, and cultivation requirements. Pineapples are perennial, herbaceous plants with bright green, spiny leaves that form a rosette. They thrive in USDA hardiness zones 10 through 11 and are used for ornamental purposes as well as fruit production. The plant prefers well-drained soil and partial shade but can tolerate full sun. Propagation is typically done by dividing suckers or rooting the leafy tops of mature fruits. Common pests include mites, scales, and mealy bugs, though no major diseases are noted. The document also highlights the aesthetic appeal of pineapples in landscaping and their compatibility with various companion plants. Original publication date September 1999.